Morphological responses of maize hybrids under competition with hairy beggarticks - Galon, Leandro (2022)
The study of competitive interactions between crops and weeds can be an important tool in integrated weed management. The objective of this work was to evaluate the competitive ability of maize hybrids in the presence of hairy beggarticks, testing different proportions of plants in the associations. For maize hybrids (Dekalb 230 PRO3, Pioneer 30F53 VYH, Brevant 2B433 PW, and Syngenta 505 VIP3) and for hairy beggarticks, the final density was 20 individuals pot-1, which was determined in preliminary experiments. Experiments were carried out on a substitutive series, on different combinations of the species, varying the relative proportions (100:0, 75:25, 50:50, 25:75, and 0:100%). The analysis of species competitiveness was performed using diagrams applied to the substitutive experiments and relative competitiveness indices. The maize hybrids showed less loss when reducing the morphological variables of the hairy beggarticks and demonstrated superiority in competitive ability in relation to the weed. Competition occurred between maize hybrids in the presence of hairy beggarticks, being negatively affected, regardless of the proportion of plants, causing reductions in plant height, stem diameter, leaf area, and dry mass. An average reduction of 10% and 86% of the MS of maize hybrids and weed was observed, respectively, when comparing the absence of competition with any associated densities, intraspecific competition being more harmful than interspecific. Maize hybrids and hairy beggarticks compete for the same environmental resources, with the crop being more competitive than the competitor.